Practical journalism : - Sissons, Helen (Sage Publication, 2006)
The chapters of Practical Journalism: How to Write News are colorful quilts of assertions, examples, anecdotes and case studies that bring to life the practice of good news writing and offer insights into the profession of journalism. Each ends with review questions, exercises and further reading…[This book] has much to offer to media and journalism students as well as working professionals, especially those in transition from one media specialization to another